The role of transformational leadership in enhancing organizational reputation A field study on administrative staff in health affairs in Jeddah - Alsulami, Mohammed Khalid Mohammed; Shuaibi, Faisal Ahmed Abed (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aimed to identify the role of transformational leadership in its various dimensions (ideal influence, inspirational motivation, intellectual stimulation, taking into account individual feelings) in enhancing the organizational reputation of the administrative staff in health affairs in Jeddah Governorate. The researcher relied on the analytical descriptive approach. The study population consisted of health affairs employees in Jeddah Governorate, where the sample size was (150) employees out of a total of (200) employees, and the questionnaire was used as a tool for the study. That the leader exceeds his own interests in order to achieve the general interest of the work, and that was with an arithmetic mean of (2.07). Leadership in health affairs depends on the quality of service in health affairs on the grounds that health affairs in Jeddah are interested in providing their best services in order to achieve their goals, with an arithmetic mean of (2.02), and among the most important recommendations of the study: the need to educate employees at all administrative levels about the importance of transformational leadership and assistance In developing their transformational leadership skills, it is necessary for administrative leaders to implement the characteristics of transformational leadership as a whole, given its impact on enhancing organizational commitment, increasing organizational commitment among employees by promoting a culture of love of work and cooperation, and enhancing a sense of belonging by providing material and moral incentives to the most committed employees.